Fine scale alpha precipitation in Ti-19at.%v in the absence of influence from omega precipitates. (15th April 2021) - Sharma, A.; Soni, V.; Dasari, S.; Mantri, S.A.; Zheng, Y.; Fraser, H.; Banerjee, R.
Abstract: While the isothermal omega-assisted mechanism of homogeneously distributed fine scale alpha precipitation has been well-documented in several titanium alloys, including Ti-19at%V (Ti-20wt%V), this paper reports that a similar type of alpha precipitation may occur in the absence of any direct or indirect influence of omega precipitates. Rapid heating of a beta solution-treated and quenched Ti-19at.%V alloy to 500 °C results in destabilization of the congruent athermal omega precipitates, followed by the development of compositional fluctuations in the form of Ti-rich or V-depleted pockets during isothermal holding, as revealed by atom probe tomography. These pockets possibly result from beta phase separation and may subsequently act as homogeneously distributed alpha nucleation sites. Graphical abstract: Image, graphical abstract